Study on traditional method by using orange peels fermentation as an alternative in sullage treatment / Nor Aqilah Mohamad Alias - Mohamad Alias, Nor Aqilah (2012)
This study was conducted to explore the feasibility of using orange peels fermentation to treat sullage. The enzyme was prepared from orange dregs, kitchen waste, molasses and water and capable of having reinforcing and cleaning function to work with nature. In this study, sullage was collected at open drainage at Bandar Puncak Alam, which focused at the Fasa 2, Shah Alam 2 and UiTM Puncak Alam and enzyme dosage determinations were done at laboratory scale. Sullage collected were analysed for BOD, COD, SS and O&G. From the result obtained all samples treated using orange peels fermentation prepared shows removal of BOD, COD and oil and grease almost 95%, then SS was 93% after 7 days of treatment with different dosage of enzyme. The significant correlation between untreated sullage and treated sullage using the enzyme has the result, p-value less than 0.05. It was found that the enzyme is capable in parameter in sullage. This study shows the potential of this method as a pretreatment step in conventional biological treatment.